2019
DOI: 10.3389/fmicb.2019.00170
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Bacteria Associated With Stainless Steel Ennoblement in Seawater

Abstract: Microorganisms can increase the open-circuit potential of stainless steel immersed in seawater of several hundred millivolts in a phenomenon called ennoblement. It raises the chance of corrosion as the open-circuit potential may go over the pitting corrosion potential. Despite the large impact of the ennoblement, no unifying mechanisms have been described as responsible for the phenomenon. Here we show that the strict electrotroph bacterium “Candidatus Tenderia electrophaga” is detected as an ennoblement bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Above 100 ppb of DOC, biofilm‐induced ennoblement was detected, increasing the risk of localized corrosion, and therefore promoting the use of more resistant alloys. The bacteria correlated with the ennoblement were related to hydrocarbon‐degrading bacteria, which were also found in another study about the role of temperature on the bacteria‐induced ennoblement, and associated with electroactive bacteria by other authors . Future studies should consider and further investigate the role of hydrocarbon‐degrading bacteria to understand their relation with the ennoblement of stainless steel.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Above 100 ppb of DOC, biofilm‐induced ennoblement was detected, increasing the risk of localized corrosion, and therefore promoting the use of more resistant alloys. The bacteria correlated with the ennoblement were related to hydrocarbon‐degrading bacteria, which were also found in another study about the role of temperature on the bacteria‐induced ennoblement, and associated with electroactive bacteria by other authors . Future studies should consider and further investigate the role of hydrocarbon‐degrading bacteria to understand their relation with the ennoblement of stainless steel.…”
Section: Discussionsupporting
confidence: 76%
“…Among the biomarkers, some are related to the known hydrocarbon‐degrading bacteria like Alcanivorax , Polycyclovorans , Algiphilus , and Thalassolituus . It should be noticed that this type of bacteria was also identified in a study about the temperature effect on stainless steel ennoblement . A member of the Alcanivoraceae family was also found in a biocathode experiment where bacteria are fed by a cathode as a sole electron donor source .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This study showed a negative correlation between bacterial growth on the working electrode surface and OCP, with a significant reduction of this latter during the exponential phase. Previous studies demonstrated that the direction of the potential change depends on the microorganism, the material where the biofilm develops and the environment [42,56]. Here, the OCP shift towards more negative values as the bacterial concentration increases may be explained by the interaction of a variety of factors.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, biocorrosion of SS has been linked with the action of autotrophic metabolism [36][37][38]. This type of corrosion is frequently associated with the ennoblement of the OCP involving iron-oxidizing bacteria, manganese-oxidizing bacteria [36,38], and, more recently, electro-autotrophic bacteria able to use an electrode (i.e., a SS coupon) as the electron donor to reduce oxygen [37,39,40]. Furthermore, the ennoblement of SS plates exposed to natural seawater typically shifts the OCP by +200 to +300 mV (vs. Ag/AgCl), bringing it closer to the pitting corrosion potential [37].…”
Section: Electrode Deteriorationmentioning
confidence: 99%